A synthetic and crystal structure study of a collection of coordination polymers based on alkaline aroylhydrazonates. (4th November 2015) - Specklin, David; Mameri, Samir; Loukopoulos, Edward; Kostakis, George E.; Welter, Richard
Graphical abstract: Selected aroylhydrazone molecules give with alkaline ions unexpected coordination polymers with various dimensionalities. One of them shows a rare and porous crystal structure with a 40% unoccupied volume suitable for potential gas absorption application properties. Abstract: The reactions of two aroylhydrazone ligands H2 L S and H2 L Ac with alkaline Li(I), Na(I), K(I) and Ba(II) metal ions afforded nine new coordination polymers with different dimensionalities. These illustrate the ionic radii, the ligand substitution and the solvent influence on the formation of the final product. Interestingly, one of them shows porous structure with a 40% unoccupied volume.